Pathologist variation in reporting cervical borderline epithelial abnormalities and cervical intraepithelial neoplasia. Issue 1 (January 1995) - Creagh, T; Bridger, J E; Kupek, E; Fish, D E; Martin-Bates, E; Wilkins, M J
Abstract : AIMS--To evaluate the interobserver variation in the diagnosis of cervical intraepithelial lesions, including the new category "borderline abnormalities of uncertain significance" (BAUS) which has not been tested before. METHODS--Biopsy specimens of 122 patients were reviewed by five histopathologists and the diagnoses subjected to kappa statistical analysis. RESULTS--There was poor interobserver agreement in all categories, particularly between BAUS and normal tissue. CONCLUSIONS--The current guidelines for the histological diagnosis of cervical intraepithelial neoplasia and BAUS are poorly reproducible.